Development of Comic-Based Teaching Materials in Elementary Schools - Sri Wulan Anggraeni; Yayan Alpian; Depi Prihamdani; Tia Damayanti (Universitas Djuanda, 2023)
This research aims to produce comic-based teaching materials for elementary schools and determine the feasibility of this comic-based teaching material. This research is a type of research and development research (R&D). This research was conducted in elementary schools using fourth-grade students as research subjects. Observation, interviews, and questionnaires were used as data-collecting methods and were all descriptively examined. The findings of this study include comic-based teaching materials, in which material experts have given a feasibility rating of 91%, 93% by language experts, and 94% by media experts. The three expert assessments are included in the